Computer Vision e Imaging come “visionica”. Verso la Visual Intelligence - Arcagni, Simone (Scenari, 2021)
The contemporary pervasive and ubiquitous visual is a product by a particular eye. The Eye of the computational machine. At this “machine that looks” in the very beginning of the 80s Paul Virilio assigned functions and characters so specific to determine a paradigm shift. “Computer vision” is the discipline born within the Informatics to enable the machine to see. And becuase it represents the foundation of contemporary visual, we have the obligation to study the technological specific and the impacts it produces.